Addressing the Learning Plateau in Social Studies through Project-Based Learning in Indonesian Secondary Schools - Mayasari, Salwa; Zahrawati B, Fawziah; Ramli, Nurleli; Zurahmah, Zurahmah; Minasyan, Sona (Program Studi Tadris IPS Institut Agama Islam Negeri (IAIN) Parepare, 2025)
Background: Students often experience a learning plateau, a stagnation in progress that negatively impacts motivation and academic outcomes. Previous studies have yet to explore effective interventions to overcome this issue, particularly in social studies learning.Purpose: This study aims to identify the stages of project-based learning (PjBL) in social studies, measure students’ learning plateau levels before and after its implementation, and evaluate its effectiveness in reducing the plateau.Method: A quasi-experimental design with a one-group pretest-posttest approach was used. The participants were eighth-grade students from SMP Negeri 12 Parepare, selected through purposive sampling, in class VIII.1 serving as the experimental group. Data were collected using learning plateau measurement instruments and analysed using the Paired Samples Test and N-Gain Score.Results: The PjBL model was implemented in five stages: essential question, project planning, scheduling, monitoring, and evaluation. The results indicated a significant reduction in students’ learning plateau levels, shifting from medium–very high to low–very low categories. A significance value of 0.000 in the Paired Samples Test confirmed the difference, while the average N-Gain Score was 0.29.Theoretical implication: These findings support the effectiveness of PjBL in addressing learning stagnation and contribute to the broader pedagogical discourse on active learning models.Practical implication: The results suggest that PjBL can be adopted in classroom practice to enhance student motivation and learning outcomes in social studies, particularly at the junior high school level.